Methods for additive hydration allowing observation of fully hydrated state of wet samples in environmental SEM - Nedela, Vilém (Microscopy research and technique, 2007)
Methods for additive hydration are presented that enable longtime observation of very wet biological specimens in an environmental scanning electron microscope. The changes of structure due to dehydration for specimens placed on a Peltier-cooled holder, put on a special agar base or embedded in it or blown over by water vapor are compared. The degree of dehydration damage of the observed specimen structures is evaluated and compared with the structure of a nondestructively dried specimen, prepared by the critical point drying method.
Keywords: agar; Animals; Cryoelectron Microscopy; Microscopy, Electron, Scanning; tenké střevo; Agar; elektronová kryomikroskopie; životní prostředí; zvířata; Water; Intestine, Small; Environment; voda; mikroskopie elektronová rastrovací